(untitled) (Revista horizonte, 2013)
Pregnancy is characterized by a number of physiological, psychological, emotional and mechanic changes that can affect health. The objective of this research was to analyze postural balance per quarter of pregnancy and its relation with the level of physical activity and BMI. Non-experimental, longitudinal and correlative methodology was used. The sample was of 25 women between 20 and 30 years old, randomly selected. The behavior of the pressure center from the technique of static posturography. The obtained results show significant differences (p<0.05) between the quarters of pregnancy under conditions of eyes closed facing forward, no correlations between BMI and postural balance. They conclude significant differences in anthropometric and postural balance between the respective trimesters of pregnancy.